Pattern and Diagnosis of Solid Testicular Swellings and it’s Management Outcome - Jamshed Bashir, Mushtaque Ahmed Abbasi, Shaheen Gul Bhatti, Shahnawaz Khatti, Aftab Soomro, Muhammad Fahim Ahsan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of the clinical pattern and diagnosis of various types of solid testicular swellings and its management outcomes. Materials and methods: This prospective cross-sectional study was done at the surgery department of Muhammad Medical College, Mirpur Khas. Cases with different presentations raising suspicion about the disease were admitted to the hospital from OPD after recording the detailed history and clinical examination. All the patients presenting with solid testicular swellings underwent inguinal exploration through an incision above the inguinal ligament, regardless of age, were included. After taking verbal informed consent, all the cases underwent testicular biopsies, and specimens were sent to the diagnostic laboratory for histopathological diagnosis. Patients having neoplastic testicular changes were referred, and patients with non-neoplastic testicular swellings lesions were treated conservatively or surgically as per indications. The data and records of all the patients were taken and maintained by the study proforma. Results: A total of 50 cases of solid testicular swellings were studied; their mean age was 48.45+7.23 years. Painless enlargement was present in 70% of cases, enlargement was usually gradual with a feeling of heaviness, followed by painful enlargement in 10.0% of cases. 20(40%) patients were diagnosed as neoplastic testicular swellings, and 30(60%) patients had non-neoplastic swellings. Among 30 cases of testicular swellings, 40.0% had orchitis, 8.0% had trauma, Epididymo-orchitis 12.0%, testicular tuberculosis was in 4.0%, and 1 (2%) had mumps orchitis. All the non-neoplastic lesions were treated successfully and neoplastic lesions cases were referred for further treatment. Conclusion: As per the study conclusion, painless enlargement (usually gradual with the feeling of heaviness) was observed to be the most common clinical feature. However, orchitis, epididymo-orchitis, and tuberculosis of the testis seemed to be the most common diagnoses among non-neoplastic cases. Neoplastic lesions were frequently high. Keywords: Testicles, swelling, features, diagnosis